KUMPULAN CERPEN DI TUBUH TARRA DALAM RAHIM POHON SEBAGAI MATERI AJAR SASTRA: GAYA BAHASA DAN PENDIDIKAN KARAKTER - Rimadani Santiningrum; Budhi Setiawan; Sri Hastuti (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This research aimed at describing and explaining about (1) the style of language used in the Short Story of Di Tubuh Tara, Dalam Rahim Pohon; (2) the value of character education contained in Di Tubuh Tara, Dalam Rahim Pohon; (3) the relevance of the Short Story in Di Tubuh Tara, Dalam Rahim Pohon as a literary learning material. The results of this study indicate that, (1) language style there are 35 data, namely simile; metaphor; personification; allegory; hyperbole; satire; irony; pleonase; periphrasis. (2) The value of character education there are 20 data, that is social care; honest; religious; responsible; curiosity; like to read; environmental care; love the homeland; appreciate achievement; hard work; independent; spirit of nationality; creative; love peace. (3) A collection of short stories In Tara's Body In The Womb Tree is one of a collection of short stories that can be made as teaching material at school. Because in addition to the collection of short stories that have a beautiful but easy to understand language style, the collection of short stories also have a different theme from one work to another, and in accordance with the subjects of Indonesian language, literary learning, especially the appreciation of short stories in high school.